Study of the production of charged pions, kaons, and protons in pPb collisions at [Formula: see text]5.02[Formula: see text] - CMS Collaboration; Chatrchyan, S; Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; et al. (The European physical journal. C, Particles and fields, 2014)
Spectra of identified charged hadrons are measured in pPb collisions with the CMS detector at the LHC at [Formula: see text]. Charged pions, kaons, and protons in the transverse-momentum range [Formula: see text]-1.7[Formula: see text] and laboratory rapidity [Formula: see text] are identified via their energy loss in the silicon tracker. The average [Formula: see text] increases with particle mass and the charged multiplicity of the event. The increase of the average [Formula: see text] with charged multiplicity is greater for heavier hadrons. Comparisons to Monte Carlo event generators reveal that Epos Lhc, which incorporates additional hydrodynamic evolution of the created system, is able to reproduce most of the data features, unlike Hijing and Ampt. The [Formula: see text] spectra and integrated yields are also compared to those measured in pp and PbPb collisions at various energies. The average transverse momentum and particle ratio measurements indicate that particle production at LHC energies is strongly correlated with event particle multiplicity.